Stability of Fodder Yield and its Quality Traits in Forage Sorghum - Patel, P R; Chauhan, R M; Jain, S K (Annals of Arid Zone, 2019)
The present study was undertaken with a view to know the G × E interactions and stability parameters in newly developed hybrids of forage sorghum for fodder yield and quality traits. The newly developed 60 hybrids, 19 parents and 3 checks were evaluated in a randomized block design with three replications during summer and kharif 2013 with two different dates in each season. Analysis of variance in individual environment as well as on pooled basis revealed highly significant differences among genotypes, parents and hybrids for all the traits. Stability analysis indicated important role of linear and non-linear components in the contribution of total G × E interaction. The linear portion was considerably high for green and dry fodder yield plant-1, brix per cent, HCN content and crude protein content. Results revealed that the prediction of performance of genotypes over environments based on regression analysis could be reliable. The magnitude of non-linear component was higher for shoot fly dead heart percentage indicated greater importance of non-linear portion in building-up total G × E interaction for this trait. The hybrid 27A × SRF 323 was more suitable specifically under good farming conditions for green and dry fodder yield plant-1 and had significant bi above unity, non-significant S2di and high mean value. Hybrids 27A × SPV 2113 and 27A × SRF 327 on the other hand were more suitable specifically under poor farming situation for green and dry fodder yield plant-1 because, they had high mean, significant bi ≤ unity and non-significant S2di. For quality characters viz., HCN content and crude protein content, hybrids 9A × SRF 331 and 104A × SPV 2113 were found stable. Thus, these hybrids can be exploited commercially for high quality fodder after testing in wide range of environments. Key words: Environment, G × E interaction, sorghum bicolor, stability analysis.